Health and development: scenario in top and bottom 20*2 countries - Dalal, Koustuv (Socialmedicinsk tidskrift, 2018)
Encouraged by the philosophy of Hans Rosling, the current study has tried to visualize development and health perspectives of the bottom 20 and top 20 countries ranked by health access quality (HAQ) index based on Socio-demographic Index (SDI), during last two and half decades (1990-2015). Also, the study has included BRICS countries (Brazil, Russia, India, China and South Africa) and the USA. The study has used secondary data from UNDP, WHO, World Bank and Global Burden of Disease and risk factor studies. Healthcare, health systems and development scenario of bottom 20 and top 20 countries ranked by HAQ index 2015 under SDI quartiles and BRICS countries and USA are presented in three different tables. It is evident that HAQ based on SDI quartiles reflects the better development and health outcomes. Instead of only 46 countries, more countries should be included and more health outcomes could be included in future studies.